Storage requirements in a 100% renewable electricity system: Extreme events and inter-annual variability - Oliver Ruhnau; Staffan Qvist (ZBW - Leibniz Information Centre for Economics, 2021)
In the context of 100% renewable electricity systems, prolonged periods with persistently scarce supply from wind and solar resources have received increasing academic and political attention. This article explores how such scarcity periods relate to energy storage requirements. To this end, we contrast results from a time series analysis with those from a system cost optimization model, based on a German 100% renewable case study using 35 years of hourly time series data. While our time series analysis supports previous findings that periods with persistently scarce supply last no longer than two weeks, we find that the maximum energy deficit occurs over a much longer period of nine weeks. This is because multiple scarce periods can closely follow each other. When considering storage losses and charging limitations, the period defining storage requirements extends over as much as 12 weeks. For this longer period, the cost-optimal storage capacity is about three times larger compared to the energy deficit of the scarcest two weeks. Adding other sources of flexibility for the example of bioenergy, the duration of period that defines storage requirements lengthens to more than one year. When optimizing system costs based on single years rather than a multi-year time series, we find substantial inter-annual variation in storage requirements with the most extreme year needing more than twice as much storage as the average year. We conclude that focusing on short-duration extreme events or single years can lead to an underestimation of storage requirements and costs of a 100 % renewable system.
Additional information: Please cite as: Ruhnau, O., Qvist, S. (2022): “Storage requirements in a 100% renewable electricity system: Extreme events and inter-annual variability”, Environmental Research Letters, https://doi.org/10.1088/1748-9326/ac4dc8; More recent version: https://doi.org/10.1088/1748-9326/ac4dc8
Keywords: Q4; Q40; Q41; Q42; 330; Renewable energy; Wind and solar power; Inter-annual variability; Low-wind events; Dunkelflaute; Electricity system; Energy storage; Hydrogen; Batteries